Nicotinamide Supplementation Attenuates Renal Interstitial Fibrosis via Boosting the Activity of Sirtuins - Xin Zhen; Shaowu Zhang; Feifei Xie; Miaomiao Zhou; Zheng Hu; Fengxin Zhu; Jing Nie (Karger Publishers, 2021)
Background: Progressive tubulointerstitial fibrosis (TIF) is the final common pathway leading to ESRD. There is an urgent need to develop effective approaches slowing the progression of TIF. Previous studies showed that systemic supplementation of nicotinamide (NAM) increases renal NAD+ and reverses ischemic-reperfusion induced acute renal injury. However, the role and mechanism of NAM in TIF has been unclear. Methods: In vivo, we injected NAM (0.25 mg/g) 3 days before unilateral ureter obstruction (UUO) till day 7 post-operation. In vitro, mouse primary proximal tubular epithelial cells (PTCs), rat renal NRK-49F cells, and human renal proximal tubular epithelial cell (HK-2) were pretreated with the indicated concentration of NAM 1 h before incubation with transform growth factor-β1 (TGF-β1) or aristolochic acid (AA) for 24 or 48 h. To evaluate the role of sirtuins (SIRTs), PTCs were pretreated with EX527 or resveratrol 30 min before incubation with NAM and TGF-β1. Results: In the present study, we demonstrated that NAM supplementation prevented UUO-induced TIF, and AA-induced renal injury. NAM also decreased the expression of pro-fibrotic proteins and pro-inflammatory cytokines (IL-6 and TNF-α) and attenuated interstitial inflammation. In vitro experiment showed that, NAM inhibited AA-induced G2/M arrest of HK-2 cells by downregulating the expression of cyclin G1, a target gene of p53. In addition, NAM inhibited TGF-β1-induced fibroblast proliferation and activation shown as downregulated expression of collagen I, fibronectin, PCNA, cyclin D1, IL-6, and TNF-α. NAM decreased the acetylation of Smad3 and p53. EX527, an inhibitor of SIRT1, reversed the effect of NAM on TGF-β1-induced matrix protein production. However, resveratrol, a SIRT1 activator, did not further boost the protective effect of NAM on reducing matrix protein production. Conclusions: Taken together, these data indicate that NAM supplementation could inhibit TIF at least partially by boosting the activity of sirtuins.